Use of iStent as a Standalone Operation in Patients with Open-Angle Glaucoma. (25th May 2020) - Chen, Yu-Yen; Lai, Yun-Ju; Yen, Yung-Feng; Huang, Li-Ying
Abstract : Purpose . The iStent provides a direct pathway for aqueous outflow from the anterior chamber to Schlemm's canal in patients with open-angle glaucoma (OAG). We performed a meta-analysis to evaluate the effectiveness of iStent as a standalone operation in patients with OAG in reducing the intraocular pressure (IOP) and the number of topical glaucoma medications. Methods . We searched various databases between January 1, 2000, and September 30, 2019, and included only peer-reviewed, prospective, or retrospective clinical studies in our analyses. Details regarding the IOP and the number of medications at baseline and end point were recorded from each study. Standardized mean differences (SMDs) of IOP and medication numbers were calculated. Furthermore, the success rate (the proportion of IOP ≤18 mmHg and IOP reduction ≥20% at end point) and the complication rate were also summarized. Finally, a subgroup analysis was done based on the iStent generation (first and second), follow-up duration (≤6, 6–18, 18–36, and >36 months), and iStent number (one, two, and three). The outcome measures were aggregated SMDs computed from each study. Results . A total of 17 studies with 978 eyes were included in this analysis. All studies demonstrated a reduction in IOP after iStent implantation. Aggregated SMDs of IOP revealed a significant reduction (SMD = −2.64, 95% confidence interval (CI): −3.21 to −2.07). The success rate was significantly good, and most of the complication rates were low. The number of medications was also significantly reduced (SMD = −1.71, 95% CI: −2.18 to −1.24). The subgroup analysis revealed a reduction in IOP and medication burden in each category of iStent generation, follow-up duration of up to 42 months, and iStent numbers. Conclusion . Use of iStent as a standalone procedure does reduce the IOP and the number of glaucoma medications. The benefit of iStent lasts for at least 42 months.